Strategies for efficient management of islamic education budgets to improve the quality and accountability of islamic educational institutions - Nabilah, Nur Rahma (Maliki Interdisciplinary Journal, 2026)
The management of education budgets is a key aspect of improving the quality and accountability of Islamic educational institutions. Amid limited funds and government policies aimed at improving the efficiency of education budgets, Islamic educational institutions are required to manage their financial resources effectively, efficiently, transparently, and responsibly. This study aims to analyze efficient Islamic education budget management strategies for improving the quality and accountability of educational institutions. The method used in this study is a literature review (library research) examining various literature, scientific journals, and regulations related to Islamic education funding. The results of the study indicate that the funding sources for Islamic educational institutions come from the government, the community, and the private sector. Effective budget management strategies can be implemented through thorough cost planning, the application of digital-based monitoring and implementation, training for financial staff, and periodic budget evaluations. Additionally, budget management from an Islamic education perspective must be grounded in the values of trustworthiness, honesty, transparency, and accountability. By implementing these strategies, Islamic educational institutions can improve budget efficiency, minimize waste, strengthen public accountability, and continuously improve the quality of educational services.